Early medieval artistic styles in the Romanesque : 'archaic' architectural sculpture in 11th-13th century Tuscany - Daltun, Eoghan (Trinity College (Dublin, Ireland). Department of History of Art and Architecture, 2007)
This dissertation deals with a type of sculpture that occurs in many Romanesque churches in Tuscany, whose most essential characteristic is the recreation of styles prevalent in early medieval metalwork and marble relief carving. Several established theories usually employed to explain the phenomenon, such as the belief that migrant sculptors from Lombardy were responsible, are shown to be generally unsatisfactory. Parallels and differences with early medieval art are explored, finding that the aim of ’archaic’ Romanesque sculpture was to provide an easily comprehensible reference to the Langobardic era, rather than to faithfully recreate its forms. While the evidence is not conclusive, it favours the possibility that 'archaic' sculpture constituted a revival, rather than a seamless continuation, of early medieval sculptural style and technique. The present study investigates the role of reused material - spolia - in the transmission of, and predilection for, earlier styles. Contemporary practices regarding the reuse of classical sculptural elements and their style in Pisa and other communal city-states is related to issues of ideology and identity. An almost analogous situation is described in rural Tuscany, where the feudal elite overwhelmingly professed a 'Langobardic' identity. The roots and rise to power of this group are studied. The latter is shown to have been almost wholly a result of the ability to gain control and ownership of Church property, particularly rural pievi (parish churches), exactly the type of monuments in which 'archaic' sculpture chiefly occurs. The advent of the communes - who invariably emphasised illusory classical origins and culture - and the serious challenge they presented to the position of the feudal class are shown to have encouraged claims to an alternative, Langobardic, 'nationality'. Such a strategy, designed to reinforce class legitimacy and solidarity, is related to similar patterns in the south of the peninsula, where rump elements of the Langobardic state sought to resist their decline in fortunes through appeals to Langobardic nationalism. Such prevailing ideological circumstances are found to have been reflected in sculpture and other artistic media in these areas, just as in Pisa and the other city-states. On this basis, it is posited that Tuscan 'archaic' sculpture is similarly the artistic manifestation of a widespread sense of Langobardic identity on the part of the seigneurial class. Finally, the expression of ethnic identity, whether real or invented, through the use of early medieval models in Romanesque sculpture is demonstrated to have been common in several other areas of western Europe.
Keywords: History of Art and Architecture, M.Litt.; M.Litt. Trinity College Dublin